Publisher Correction: 3D Shape Modeling for Cell Nuclear Morphological Analysis and Classification. Issue 1 (December 2018) - Kalinin, Alexandr; Allyn-Feuer, Ari; Ade, Alex; Fon, Gordon-Victor; Meixner, Walter; Dilworth, David; Husain, Syed; de Wet, Jeffrey; Higgins, Gerald; Zheng, Gen; Creekmore, Amy; Wiley, John; et al.
A correction to this article has been published and is linked from the HTML and PDF versions of this paper. The error has been fixed in the paper.